IMPLEMENTASI PERATURAN DAERAH NOMOR 5 TAHUN 2006 DALAM PEMEKARAN DISTRIK & KAMPUNG DI KABUPATEN YAHUKIMO - Meage, Thinus; Ohoiwutun, Yosephina; Aedah, Nur (Universitas Cenderawasih, 2025)
The assessment of regional expansion policy is important as an effort to equalize development and improve public services in underdeveloped and remote areas. This study aims to describe and analyze the implementation of Regional Regulation No. 5 of 2006 concerning the establishment of 51 districts, 517 villages, and 1 sub-district in Yahukimo Regency as an indicator of community development. The urgency of this research is to evaluate the effectiveness of regional expansion in overcoming inequality and improving public services in underdeveloped areas. The focus of the study includes policy content, policy environment, policy outcomes, and factors that support and hinder its implementation. This study uses a descriptive qualitative approach with a case study method. Data collection techniques include in-depth interviews, participatory observation, and documentation study, while data analysis techniques are carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the policy has not been fully optimized. Although there has been an expansion of government administration to remote areas, there are still significant obstacles such as limited infrastructure, minimal human resource capacity, and weak coordination between districts. The policy environment shows that the influence of local power and the involvement of political elites is quite dominant, but this has not been balanced by the active participation of grassroots communities. In terms of policy outcomes, there have been changes in the structure of government, but these have not been significant in accelerating public services and community welfare. This study recommends the need to strengthen the capacity of village officials, develop a roadmap for development based on customary territories, and implement integrated evaluative oversight across all levels of government.